PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2022 - Agustriana, Novia; Wijaya, Rico; Ridwan, Muhammad (Jambi Accounting Review (JAR), 2024)
Financial distress is one of the characteristics of a company that is facing financial difficulties. Various ways are needed to prevent companies from falling into financial distress, and one of the measurement tools that can be used to predict financial distress is through measuring financial performance in financial statements with financial ratio calculations. This study aims to determine and analyze the effect of profitability, liquidity, leverage, activity and growth on financial distress both simultaneously and partially. This type of research is quantitative research with the documentation method. The population is 23 companies with a sampling technique, namely purposive sampling, so that 20 companies are obtained as samples. Data analysis using logistic regression analysis using SPSS version 29. The results showed that profitability, liquidity, leverage, activity and growth simultaneously affect financial distress. Liquidity has a significant effect partially on financial distress. While profitability, leverage, activity and growth have no significant effect on financial distress.